2018
DOI: 10.1111/maps.13179
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic investigation of shatter cone melt films recovered from MEMIN impact experiments in sandstone and iSALE modeling of their formation boundary conditions

Abstract: Shatter cones are diagnostic for the recognition of meteorite impact craters. They are unambiguously identifiable in the field and the only macroscopic shock deformation feature. However, the physical boundary conditions and exact formation mechanism(s) are still a subject of debate. Melt films found on shatter cone surfaces may allow the constraint of pressure–temperature conditions during or immediately after their formation. Within the framework of the MEMIN research group, we recovered 24 shatter cone frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In quartz grains experimentally shocked at 5 to 17.5 GPa, Fazio et al [5] observed glass veins composed of amorphous silica generally thicker than 50 nm, extending several microns in length. Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. Laboratory shock experiments by Martinelli et al [79] used quartz crystals with a minimum diameter of 3400 µm, larger than we tested.…”
Section: Previous Studies Of Amorphous Silica In Quartz Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In quartz grains experimentally shocked at 5 to 17.5 GPa, Fazio et al [5] observed glass veins composed of amorphous silica generally thicker than 50 nm, extending several microns in length. Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. Laboratory shock experiments by Martinelli et al [79] used quartz crystals with a minimum diameter of 3400 µm, larger than we tested.…”
Section: Previous Studies Of Amorphous Silica In Quartz Grainsmentioning
confidence: 99%
“…For example, in quartz grains experimentally shocked at 5 to 17.5 GPa, Fazio et al [5] observed glass veins composed of amorphous silica extending across several microns in length and generally thicker than 50 nm. Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. Shatter cones are considered to be a classic impact indicator.…”
Section: Introductionmentioning
confidence: 99%
“…In quartz grains experimentally shocked at 5 to 17.5 GPa, Fazio et al [5] observed glass veins composed of amorphous silica that extend across several microns in length and that are generally thicker than 50 nm. Wilk et al [6] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa. In addition, Carl et al [7] conducted experiments demonstrating that extensive amorphization of quartz begins at ~10 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In quartz grains experimentally shocked at 5 to 17.5 GPa, Fazio et al [88] observed glass veins composed of amorphous silica extending several microns in length and generally thicker than 50 nm. • Wilk et al [89] found amorphous silica in experimentally shocked rocks called shatter cones that formed at low shock pressures of 0.5-5 GPa.…”
mentioning
confidence: 99%